Exploring the 'prehistory' of the equatorial stratosphere with observations following major volcanic eruptions. (24th October 2017) - Hamilton, Kevin; Sakazaki, T.
Abstract : Since 1953 meteorological balloon soundings from low‐latitude stations have revealed that the prevailing winds in the equatorial stratosphere undergo a remarkable alternation between strong easterlies and strong westerlies in a cycle with a period averaging ~27 months. To understand the full range of the behavior of this 'quasibiennial oscillation' (QBO), attempts have been made to reconstruct the equatorial stratospheric winds in the pre‐1953 era. This paper considers one approach to estimating winds in the distant past, through analysis of observations of the drift of stratospheric aerosol after volcanic eruptions. We review the famous case of the 1883 eruption of Krakatau and also deduce the winds following the major Caribbean island eruptions in May 1902. This 1902 wind estimate provides independent confirmation of a recently published reconstruction of the QBO. Abstract : This paper considers one approach to estimating winds in the equatorial stratosphere in the period before regular balloon observations, namely through analysis of observations of the drift of stratospheric aerosol after volcanic eruptions. We review the famous case of the 1883 eruption of Krakatau and also deduce the winds following the major Caribbean island eruptions in May 1902. This 1902 wind estimate provides independent confirmation of a recently published reconstruction of the QBO.